2004
DOI: 10.1038/nbt961
|View full text |Cite
|
Sign up to set email alerts
|

Encoded self-assembling chemical libraries

Abstract: The isolation of molecules capable of high-affinity and specific binding to biological targets is a central problem in chemistry, biology and pharmaceutical sciences. Here we describe the use of encoded self-assembling chemical (ESAC) libraries for the facile identification of molecules that bind macromolecular targets. ESAC technology uses libraries of organic molecules linked to individual oligonucleotides that mediate the self-assembly of the library and provide a code associated with each organic molecule.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
253
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 323 publications
(258 citation statements)
references
References 31 publications
0
253
0
4
Order By: Relevance
“…546 DNA-based libraries have been useful in identifying inhibitors of BCA. 414,547 Doyon et al reported a technique for using BCA to enrich the concentration of their target inhibitors within a small library of inhibitors. 547 They linked each inhibitor to a unique sequence of DNA, which served as a means to amplify and identify the enriched species.…”
Section: Combinatorial Approaches To Ligandmentioning
confidence: 99%
“…546 DNA-based libraries have been useful in identifying inhibitors of BCA. 414,547 Doyon et al reported a technique for using BCA to enrich the concentration of their target inhibitors within a small library of inhibitors. 547 They linked each inhibitor to a unique sequence of DNA, which served as a means to amplify and identify the enriched species.…”
Section: Combinatorial Approaches To Ligandmentioning
confidence: 99%
“…[4] Such DNAencoded chemical libraries may be constructed as singlepharmacophore libraries (in which suitable chemical moieties are added in a stepwise fashion to molecular scaffolds [5][6][7][8] ) or as dual-pharmacophore chemical libraries (also termed encoded self-assembling chemical (ESAC) libraries [9,10] ). This second methodology is particularly suited for the improvement of binding affinity and specificity, starting from lead compounds of modest potency.…”
mentioning
confidence: 99%
“…Both DNA and PNA platforms have been used successfully to encode small molecule libraries with the first libraries reported in 2004. [25][26][27][28][29][30] PNA encoded synthesis (PES) is facilitated by the fact that it can be carried out using conventional solid phase synthesis. [31] Starting with a resin loaded with a bifunctional linker (such as lysine) bearing orthogonal protecting groups, the synthesis of the small molecule can be carried out alongside the PNA synthesis ( Fig.…”
Section: Combinatorial Synthesis Of Encoded Librariesmentioning
confidence: 99%
“…The strategy was used first to pair a small library of drug fragments with a known pharmacophore to increase affinity. [30] Displaying ligands on a DNA template rather than through selfcomplementation offers the advantage that the pairing and distances are controlled through the instructions in the template. Thus, the same nucleic acid-tagged molecules can be arranged in a variety of controlled pairing and distance using a library of templates.…”
Section: Introductionmentioning
confidence: 99%